2011
DOI: 10.1007/s00606-011-0467-6
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype variability in species of the genus Zephyranthes Herb. (Amaryllidaceae–Hippeastreae)

Abstract: In this work, the cytotaxonomic implications of the chromosomal characterization of cultivated and native Zephyranthes species described in northeastern Brazil were studied. All individuals had karyotype formed by a set of metacentric chromosomes, in addition to submetacentric and acrocentric chromosomes. In Zephyranthes robusta, 2n = 12 was observed and karyotype with formula 4M ? 2SM in somatic cells, representing the most symmetric karyotype among the investigated species. Z. sylvatica showed three differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Some taxonomic groups, such as orchids of the genera Oncidium and Epidendrum Guerra, 2000, 2010), and Hoffmannseggella (Yamagishi-Costa and Forni-Martins, 2009) have a strong tendency to form polyploids in environments that experience extreme conditions of abiotic stress. Other taxonomic groups, however, such as the families Convolvulaceae (Pitrez et al, 2008) and Amaryllidaceae (Felix et al, 2011), show no apparent correlation between polyploidy and environmental stress. The evolution of plant groups by the duplication of their genomes is generally rarer in tropical regions than in temperate zones, where environmental fluctuations are more frequent and are conducive to the formation of non-reduced gametes (Leitch and Bennett, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Some taxonomic groups, such as orchids of the genera Oncidium and Epidendrum Guerra, 2000, 2010), and Hoffmannseggella (Yamagishi-Costa and Forni-Martins, 2009) have a strong tendency to form polyploids in environments that experience extreme conditions of abiotic stress. Other taxonomic groups, however, such as the families Convolvulaceae (Pitrez et al, 2008) and Amaryllidaceae (Felix et al, 2011), show no apparent correlation between polyploidy and environmental stress. The evolution of plant groups by the duplication of their genomes is generally rarer in tropical regions than in temperate zones, where environmental fluctuations are more frequent and are conducive to the formation of non-reduced gametes (Leitch and Bennett, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 2n=4x=24 in Z. carinata (tetraploid) and 2n=8x= 48 in Z. tubispatha (octaploid) represents the base number x= 6 that supports the previous findings. However, 2n=38 in Z. candida could occur as hexaploid (2n=6x=36) followed by secondary modification (hyper-aneuploidy), similarly reported by Felix et al (2011b). Because of the most frequent occurrence, it is to be expected that variation in base number might be originated from the normal ancestor having x= 6.…”
Section: Somatic and Basic Chromosome Numbermentioning
confidence: 70%
“…x=5, 7, 9, 11, 13, and15 (Naranjo 1969, Daviña andFernández 1989), however, those numbers were found to exist in very few cases. Felix et al (2011b) reported Z. robusta and Z. sylvatica as diploid, Z. rosea, Z. brachyandra and Z. grandiflora (=Z. carinata) as tetraploid considering x= 6.…”
Section: Somatic and Basic Chromosome Numbermentioning
confidence: 99%
“…The polyploid origin of plant species has been shown by classical cytogenetics, such as for the genera Psidium Linnaeus, 1753 ( Souza et al 2015 ), Claytonia Linnaeus, 1753 ( McIntyre 2012 ) and Cardamine Linnaeus, 1753 ( Marhold et al 2010 ). From the assembly of accurate karyograms using chromosomes with different levels of chromatin compaction, the type of polyploidy was also evidenced, with autopolyploidy being found in Glycine max (Linnaeus, 1753) Merrill, 1917 ( Clarindo et al 2007 ) and Zephyranthes Herbert, 1821 ( Felix et al 2011 ), and allopolyploidy in Paullinia cupana Kunth, 1821 ( Freitas et al 2007 ) and Triticum aestivum Linnaeus, 1753 ( Kamel 2006 ). Polyploidy has played a key role in plant evolution, with estimates maintaining euploidy in the ascendancy of all angiosperms ( Abbott et al 2013 , Soltis et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%